Efektivitas Variasi Konsentrasi Air Perasan Jeruk Nipis sebagai Pengganti Komposisi Larutan Turk untuk Hitung Jumlah Leukosit - Annisa, Istiana; Hasanah, Mifroh; Mahardhika, Rian Bayu Santya (Politeknik Kesehatan Kementerian Kesehatan Banten, 2024)
Standard turk solution is a solution used for manual leukocyte count examination including glacial acetic acid, gentian violet and distilled water. Lime fruit (Citrus aurantifolia swingle) is a type of orange that has a pH of 2.0. Both of these materials belong to weak acids that can lyse blood cells other than leukocytes which can be used to check leukocyte counts. The purpose of this study was to determine the effectiveness of lime juice as a substitute for turk solution with several concentrations. The research design used is descriptive. This study uses the SPSS method. The results of this study were that the sig value of the turk solution with several variations was 2% = 0.935, 3% = 0.326, 4% = 0.162 and 5% = 0.108 where all results were > 0.05 which can be concluded that there was no much difference between the control and all variation of orange juice but the highest significant variation is 2%.